2016
DOI: 10.18203/2319-2003.ijbcp20163270
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-drug interactions among hospitalized cardiac patients

Abstract: Drug-drug interactions (DDIs) represent a special category of adverse drug reactions in which the effects of one drug influence the effects of the other, thus either limiting effectiveness or inducing toxicity. Overall, 1% of hospital admissions and 16% of admissions due to ADRs can be attributed to DDIs. A higher number of DDIs is also significantly associated with longer hospitalization and higher treatment costs. 1,2 Approximately 37-60% of patients admitted to hospital may have one or more potentially inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
3
4
2
Order By: Relevance
“…The higher occurrence of pDDIs in males in our study is consistent with previously published reports. [131415] The average number of drugs prescribed/patient in our study was also similar to other studies. [1314] The similarities in observations could be due to similarities in the prescribing pattern of the medications in CVD patients.…”
Section: Discussionsupporting
confidence: 89%
“…The higher occurrence of pDDIs in males in our study is consistent with previously published reports. [131415] The average number of drugs prescribed/patient in our study was also similar to other studies. [1314] The similarities in observations could be due to similarities in the prescribing pattern of the medications in CVD patients.…”
Section: Discussionsupporting
confidence: 89%
“…Most commonly observed mechanism of drug-drug interactions in this study was pharmacodynamic as also supported by other studies. 4,5 This is in contrast to the finding reported in a few studies. [11][12][13] Polypharmacy is widely prevalent in hospitalized patients and although it poses threat to patients' overall recovery, it sometimes becomes unavoidable.…”
Section: Increase In Anti-hypertensive Effectmentioning
confidence: 59%
“…Study revealed very high prevalence of drug-drug interactions in the cardiac in-patients as supported by other studies. [4][5][6][7] The high prevalence may be due to presence of various risk factors in hospitalized patients. Elderly age group, cardiac illness and associated multiple co-morbidities which in turn lead to polypharmacy, may result into development of drug-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Binary logistic regression showed that the risk of having more than seven pDDIs was significantly higher when patients stayed at the hospital for 5-12 days compared to 1-4 days, among patients prescribed with more than nine medications compared to patients prescribed with 1-8 medications, patients having comorbid conditions compared to patients without comorbid conditions, patients with comorbid conditions like hypertension and diabetes mellitus (HTN + DM) and diabetes mellitus (DM) only compared to patients with CVD alone, and patients prescribed with narrow therapeutic index medications compared to patients not prescribed with narrow therapeutic index medications Table 8. 20 . These medical conditions seem to have a pathophysiological association with each other and are often observed to occur in the presence of one another, which might be the reason for a higher number of patients with DM and HTN as comorbidities 21 .…”
Section: Risk Factors For Pddismentioning
confidence: 99%
“…Recent studies around the world had shown the incidence of DDIs to be in the range of 21.3%-98% 16,[18][19][20] . Although a large number of studies have been conducted throughout the world assessing the DDIs in patients with CVD, there are variations in the reported rates of pDDIs.…”
mentioning
confidence: 99%